Analysis of the Relationship Between Psychological Well-Being and Decision Making in Adolescent Students - Páez-Gallego, Javier; Gallardo-López, José Alberto; López-Noguero, Fernando; Rodrigo-Moriche, María Pilar (Frontiers in Psychology, 2020)
Adolescents are frequently faced with situations in which they have to make decisions by choosing from a range of possible alternatives. In such circumstances, individual, social and environmental conditions have an impact on the choice of the final decision in light of the various options presented. The main objective of this study is to analyze the relationship between the psychological wellbeing of adolescent students and their decision-making style. The research method used corresponds to an ex post facto, quantitative, transversal, correlational and descriptive design, with an initial sample of 1,262 students from the Autonomous Region of Madrid, Spain, aged 13-19. A subsequent resampling of 385 participants was extracted from the initial sample by proportional allocation to strata (according to the levels of the variables gender, academic year and educational institution classification) to guarantee the representativeness of the population data. Two models were used for data collection. The first is a Spanish adaptation of Ryff’s Psychological Wellbeing Scale, which collects data on the psychological wellbeing variable using values given by adolescents to different situations and questions relating to their living situation, and their perception of success in everyday aspects of development and achievements. The second is a decision-making style questionnaire, Flinders Adolescent Decision Making Questionnaire (FADMQ), adapted by Friedman and Mann, which measures two major decision-making styles - adaptive and maladaptive - the former is the most optimal and desirable when making decisions which respond to criteria of rationality. The data obtained was analyzed by correlating the overall level of psychological wellbeing with the two decision-making styles. By doing so, it was observed that greater use of adaptive decision-making strategies correlates significantly with greater psychological wellbeing. In contrast, the correlation is high and negative at the intersection of the maladaptive decision-making variables and psychological wellbeing. In other words, subjects with a higher level of psychological wellbeing apply maladaptive strategies in their decision-making style to a lesser extent.